Group selection and altruistic behaviour in a plasmid-bacteria system, a probabilistic simulation (2021)
Altruism has made biologists wonder and argue for decades because at first glance it might seem to contradict Darwinian evolution, as altruistic behavior would lower the fitness of an individual while not providing any direct benefits; however, this phenomenon happens everywhere in nature, from little primates looking out for predators while their peers feed, to nesting birds that protect unrelated offspring, or even humans, where charity is only one of many examples. But even more interestingly it happens in every multicellular creature, as each individual cell limits its reproduction to ensure the survival of the larger organism (with the clear exception of cancer cells). In this text we propose to study a simple system of plasmid containing bacteria to analyse how multilevel selection can emerge and favour altruistic behavior, as it is advantageous (selfishly) for a plasmid to replicate as much as possible while at the same time causing a burden on its host, therefore diminishing its chances to replicate and grow in the bacterial population. We use a computer simulation built around a Moran process and previous knowledge on plasmid intracellular interactions to model and shed light on such an interesting and relevant dynamic.